HISTOPATHOLOGICAL PATTERNS OF CHRONIC LIVER DISEASES IN DOGS AND CATS: CORRELATION WITH LABORATORY TESTS (International Seven Journal of Multidisciplinary, 2025)
Objective: To evaluate the main histopathological patterns found in chronic liver disease (CLD) in dogs and cats and correlate them with laboratory findings, emphasizing the importance of histopathological examination for definitive diagnosis and prognosis. Chronic liver disease in small animals has diverse etiologies and slow progression, and is often diagnosed at advanced stages. This literature review analyzed national and international studies on the prevalence, morphological patterns, and clinical and laboratory implications of CHD in dogs and cats. The data show that microvascular dysplasia, chronic hepatitis, and cholangitis are among the most frequent diagnoses. The association between laboratory abnormalities, such as elevated ALT and FA, and histological findings such as fibrosis, portal inflammation, and hepatocellular degeneration, allows for better clinical management. Liver biopsy techniques (Tru-Cut®) remain essential, although complementary methods such as serum biomarkers and digital analysis are expanding. It is concluded that the integration of clinical, laboratory, and histopathological findings is indispensable for the early diagnosis and effective management of CHD in small animals.